A simple hair control approach during intra-oral surgical procedures - Chhabra, Shruti; Kumar, Yuvika Raj; Chhabra, Naveen (International Journal of Infection Control, 2010)
While the majority of post-operative infections originate from endogenous flora, nevertheless patient factors can also contribute to these infections. Facial hair around the operative field (especially hair of beard) can be a cause for post-operative infection and reduced access to the operative field. The solution to this problem is either removal of hair or application of various hair control techniques. Pre-operative hair removal has been demonstrated to actually increase the risk of post-operative infection so hair control techniques should be chosen wherever conditions permit. This technical note mentions about a very simple, economical and less time consuming method which involves the use of a face mask for controlling hair around the oral cavity that can be offered to patients who are not willing to get their hair removed due to their religious beliefs especially patients from the Sikh and Muslim community and also patients who cannot bear the increased cost of treatment due to application of some expensive hair control methods.